Integrating Environmental Principles in Sustainable Corporate Management Strategies - Denpharanto Agung Krisprimandoyo; Hendra Jayusman; Yulian Arpianto; Arif Budi Sulistyo; Bintang Simbolon (International Journal of Science and Society, 2023)
Environmental problems are important because they affect the lives of all humans. Therefore, company management needs to develop sustainable strategies. This research was carried out to look at how to integrate environmental principles into sustainable company management strategies. This study will employ a descriptive qualitative methodology. The data for this investigation is derived from diverse research findings and prior studies that remain pertinent to the current research. The results of this research then found that there were various problems faced in integrating environmental principles, such as cultural challenges, economic obstacles, and pressure from stakeholders. However, even though various challenges need to be faced, the impact of environmental integration is quite large. This includes improving the company's image, resource efficiency, and attracting investors. By using the right techniques, the environmental performance carried out by the company can be achieved well.